Optimasi Konsentrasi Ekstrak Alang-Alang (Imperata cylindrica L.) untuk Memacu Pertumbuhan dan Produksi Jagung Manis (Zea mays Saccharata Sturt) - Mayta Novaliza Isda; Wahyu Lestari; Diana Agriani (Al-Kauniyah: Jurnal Biologi, 2013)
Sweet corn (Zea mays saccharata Struts) a type of corn of high economic value, not only used for consumption also used to make syrup. Imperata is one of the weeds that interfere with crop cultivation, but efforts continue to be made use of weeds as an addition to soil organic matter. The study was conducted to determine the concentration of the extract Imperata (Imperata cylindrica L.) appropriate in the sweet corn growth and determine the concentration of extract proper Imperata in the growth and production. The research method is a Completely Randomized Design (CRD) with 9 treatments and 3 replicates. The results showed that treatment of Imperata extracts with varying concentrations significantly influenced the growth of plant height and leaf number. But not significantly to the growth of the leaf length, leaf width, stem diameter, number of rows per cob, number of seeds per row and plant dry weight. At a concentration of 200 g / 250 ml was able to reduce the vegetative and generative growth of sweet corn.